Designing highly fluorescent, arylated poly(phenylene vinylene)s of intrinsic microporosity. Issue 7 (18th December 2019) - Rodrigues, Ana Clara B.; Geisler, Isabell S.; Klein, Patrick; Pina, João; Neuhaus, Fabian J. H.; Dreher, Elke; Lehmann, Christian W.; Scherf, Ullrich; Seixas de Melo, J. Sérgio
Abstract : The design of new arylated poly(phenylene vinylene) with high fluorescence efficiency (from AIE) and intrinsic microporosity (from S BET ) is described. Abstract : Three new polymers containing tetraphenylethylene and diphenyl-dinaphthylethylene cores and their corresponding monomeric model compounds were synthesized and fully characterized aiming to investigate their photoluminescence efficiency, microporosity and Brunauer–Emmett–Teller-derived surface areas ( S BET ). Comprehensive photophysical characterization was undertaken in the solid state (powder and thin films), in tetrahydrofuran (THF) solution and in mixtures of "good" and "poor" solvent to induce aggregation (THF:water mixtures). Aggregation induced emission (AIE) was found for the tert -butyl-TPE monomer and polymer and diphenyl-dinaphthylethylene monomer with the increase of the water amount in THF:water mixtures and in the solid state. The tert -butyl substituted TPE derivatives display the highest fluorescence quantum yield ( ϕ F ) values: 0.14 to 0.30 (in powder) and 0.46 to 0.64 in thin films. In contrast, with the diphenyl-dinaphthylethylene ( meta and para -phenylene) polymers aggregation caused quenching (ACQ) occurs in THF:water mixtures ( ϕ F ≤ 0.011) and in the solid state ( ϕ F ≤ 0.012). The microporosity of the soluble conjugated polymers as potential conjugated polymers of intrinsic microporosity (cPIMs) was further investigated. The S BET of the polymers were related to their optical properties. The polymers show an attractive combination of high S BET surface area (417 m 2 g −1 ) and the occurrence of distinct AIE effects for the tert -butyl-TPE polymer while the diphenyl-dinaphthylethylene polymers do not exhibit microporosity ( S BET ≤ 17 m 2 g −1 ) and show ACQ behavior.